Orbit of comet C/1854 L1 (Klinkerfues) - Branham, Richard Lacy (2013)
Comet C/1854 L1 (Klinkerfues) is one of a large number of comets with parabolic orbits. Given that there are sufficient observations of the comet, 262 in right ascension and 260 in declination, it proves possible to calculate a better orbit. The calculations are based on a 12th order predictor–corrector method. The comet's orbit is highly elliptical, e=0.99866 and, from calculated mean errors, statistically different from a parabola. The comet will not return for at least 10,400 years and thus represents no immediate NEO threat.